Students' Difficulties in Solving HOTS-Based Mathematical Problems - Shahnaz Nurazizah; Nurul Arfinanti (Indonesian Journal of Mathematics Education, 2025)
Critical thinking is essential for solving complex problems, and mathematics provides an effective medium for developing this skill. This study aimed to identify students' difficulties in solving mathematical critical thinking problems based on Higher Order Thinking Skills (HOTS). The participant were 33 Grade X students from a senior high school in Yogyakarta. A descriptive method was employed, with data collected through tests, interviews, questionnaires, and documentation. The instrument was a HOTS-based test aligned with four indicators of mathematical critical thinking skills: interpretation, analysis, evaluation, and inference. Data analysis followed three stages: reduction, presentation, and conclusion drawing. The results revealed three levels of students' mathematical critical thinking skills: high (27.27%), moderate (51.52%), and low (21.21%). Students in the high category demonstrated strong performance across all indicators, while those in the moderate category generally understood the problems but often made mistakes in analysis and evaluation. Students in the low category encountered difficulties in all indicators, particularly in comprehending problem information, applying mathematical concepts, and formulating conclusions. These findings highlight that the main difficulties occur in the stages of interpretation, analysis, evaluation, and inference, especially among those with moderate and low skill levels.